Modified Psychological Scale for Pros-thodontic Patients - Nadira A Hatim; Monia MN Kandil; Elham Kh Al-Jamas (University of Mosul, College of Dentistry, 2012)
To aid the dentist in a more precise method for psychological and neurotic assessment of his patients, especially the edentulous; and to isolates those who may refuse the complete denture wearing for psychological reasons. Materials and methods: The study was conducted to include one hundred members, who agreed to participate in it. They were collected randomly from Dental College of Mosul University, and a Dental Health Center at Mosul City. Members were asked to answer these question-naires: Eysenck Personality Inventory; Hamilton Anxiety Scale; and Mental Health Questionnaires. Statistical analysis of questioner was done according to percentage, and prevalence . Results: The data collected from these scales undergone statistical and correlation analysis to show the frequency and prevalence for each question and the most effectible components to introduce new psychological case-sheet, briefed what most important psychological factors that could investigated by the dentist. Conclusions: A modified psychological scale was accomplished for edentulous patients. The results also revealed that the general somatic sensory symptoms, autonomic nervous symptoms, insomnia and gastro-intestinal symptoms; represented the most effective factors on the stress development, especially in the geriatrics